2016
DOI: 10.1016/j.jth.2016.02.010
|View full text |Cite
|
Sign up to set email alerts
|

International comparisons of the associations between objective measures of the built environment and transport-related walking and cycling: IPEN adult study

Abstract: Introduction Mounting evidence documents the importance of urban form for active travel, but international studies could strengthen the evidence. The aim of the study was to document the strength, shape, and generalizability of relations of objectively measured built environment variables with transport-related walking and cycling. Methods This cross-sectional study maximized variation of environments and demographics by including multiple countries and by selecting adult participants living in neighborhoods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
121
3
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(143 citation statements)
references
References 35 publications
10
121
3
3
Order By: Relevance
“…Saúde Pública 2018; 34(1):e00203116 Medium streetscape reduced by 41% and 46%, respectively, the likelihood of walking ≥ 150 min/ week and bicycling. These results differ from a study in the US cities of Seattle, San Diego, Baltimore, and Washington DC, where the overall streetscape score was positively associated with weekly frequency of active commuting (walking + bicycling) 34 . The inverse association shown in the current study may have several explanations.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Saúde Pública 2018; 34(1):e00203116 Medium streetscape reduced by 41% and 46%, respectively, the likelihood of walking ≥ 150 min/ week and bicycling. These results differ from a study in the US cities of Seattle, San Diego, Baltimore, and Washington DC, where the overall streetscape score was positively associated with weekly frequency of active commuting (walking + bicycling) 34 . The inverse association shown in the current study may have several explanations.…”
Section: Discussioncontrasting
confidence: 99%
“…Two studies tested the association between the environment's characteristics (by systematic observation) and walking and bicycling in adults 8,25 . However, these studies were done in cities in the United States, where the characteristics of the environment differ greatly in comparison to Brazilian cities 34 . For example, a multicenter study in 14 cities in 10 countries showed that the density of street intersections and mixed land use were greater in Curitiba, than in cities in New Zealand and the United States 34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies were conducted in Asia and two studies in South America. Two studies were cross-national studies, with one study [62] containing five European countries and the other one [69] containing ten countries from four continents. All the studies examined both male and female subjects.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Although her claims did not receive much attention at that time, her ideas have influenced urban design practices such as pedestrian-friendly design, mixed land use, and transit-oriented development, demonstrated by the New Urbanist movement (Calthorpe, 1993;Sternberg, 2000). In addition, research has extensively examined the associations between these components and walking activity during the last decade (Christiansen et al 2016, Duncan et al 2010and Frank et al 2006, Grasser et al, 2013Knuiman et al, 2014, Stewart et al, 2016, Sung et al, 2014.…”
Section: Introductionmentioning
confidence: 99%